ANALYTICAL FEATURES OF SYNTHETIC MDMB(N)-073F CANNABIMIMETICS AND ITS MARKERS IN BIOLOGICAL MATERIAL - S. S. Kataev; O. N. Dvorskaya; M. A. Gofenberg; A. V. Labutin; A. B. Melentyev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
The aim of the research is to study both analytical features of synthetic MDMB(N)-073F cannabimimetics of indazole carboxamides group by gas chromatography methods combined with tandem mass spectrometry (GC-MS) and high performance liquid chromatography with high-resolution mass spectrometry (HPLC-HRMS) as well as characteristics of the major MDMB(N)-073F metabolite, its glucuronide and derivatives, using gas chromatography with mass-spectrometric (GC-MS) detection and high-performance liquid chromatography (HPLC) with MS/MS mass spectrometry (HPLC-MS/MS) in urine samples to be applied in expert practice, chemical-toxicological and forensic and chemical analyses.Materials and methods. To carry out the study, the following materials were used: plant-based objects with narcotic drugs withdrawn from illegal trafficking and applied to them;. urine samples to be studied under chemical-toxicological and forensic and chemical analyses. For solid-phase epitaxy, SampliQ EVIDEX TFE cartridges - 200 mg - 3 ml (Agilent, USA) were used for sample preparation; β-glucuronidase, Type HP-2, From Helix Pomatia, 100000 UA/ml (Sigma-ALDRICH CHEMI, Germany) was used for enzymatic hydrolysis. GC-MS/MS analysis was made using Agilent 7890 gas chromatograph with a tandem quadrupolar mass-spectrometer Agilent 7000 (Agilent, США); GC-MS analysis was carrid out using gas chromatograph Agilent 7820 with mass-selective detector Agilent 5975 (Agilent, USA); HPLC-HRMS research was made on liquid chromatograph Agilent 1260 with tandem hybrid high-resolution quadrupole-time-of-flight detector Agilent 6540 (Agilent, США); liquid chromatograph Agilent 1260 with Agilent 6460 (Agilent, USA) with tandem mass-spectrometer were used for making HPLC-MS/MS research.Results. The structure of MDMB(N)-073F compound has been confirmed and an exact mass of the protonated molecule corresponding to the chemical formula C19H27FN3O3 fixed by GC-MS/MS and HPLC-HRMS methods. Spectral characteristics of MDMB(N)-073F have been given. One of the branches in MDMB(N)-073F biotransformation in the human body found out by GC-MS and HPLC-MS/MS methods, is the ester decomposition with further conjugation of the resulting acid. The product interacting with glucuronic acid, is found to be the conjugate of major MDMB(N)-073F metabolite of the Ist phase in biotransformation. Metabolites appearing due to the ester decomposition and its conjugate with glucuronic acid, are recommended to be used as markers for synthetic MDMB(N)-073F cannabimimetics in the analysis by chromatographic methods; they can be used for regular screening of biological samples.Conclusion. The research results presented here, are the following: the analytical features characteristic for synthetic MDMB(N)-073F cannabimimetics found out by gas chromatography methods combined with tandem mass spectrometry (GC-MS/ MS) and liquid chromatography of hybrid high-resolution quadrupole-time-of-flight mass spectrometry (HPLC-HRMS), as well as characteristics of major MDMB(N)-073F metabolite, its glucuronide and derivatives with the use of gas chromatography with mass-spectrometric detection (GC-MS) and liquid chromatography combined with tandem mass spectrometry (HPLC-MS/MS) in urine samples to be applied in expert practice, chemical-toxicological, forensic and chemical analyses.